Share Capital Management in the Context of Ensuring Competitive Advantages of the Retail Business Entity - A. S. Dyadin; N. V. Bobro (Law and Safety)
It has been proved that capital is a resource that is accumulated and is involved in the processes of reproduction and growth of value through mutual conversion of its various types, which are invested in the creation of assets, which is the total amount of financial resources of enterprises.